1996
DOI: 10.1074/jbc.271.1.238
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced Conformational Changes in the Apical Domain of the Chaperonin GroEL

Abstract: Although the role of nucleotides in the catalytic cycle of the GroESL chaperonin system has been extensively studied, the molecular effects of nucleotides in modulating exposure of sites on GroEL has not been thoroughly investigated. We report here that nucleotides (ATP, ADP, or adenosine 5-(␤,␥-imino)triphosphate) in the presence of Mg 2؉ make the oligomer selectively sensitive to trypsin proteolysis in a fashion suggesting conformational changes in the monomers of one heptameric ring. The site of proteolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
5
13
0
Order By: Relevance
“…These results are compatible with those reported for wild-type GroEL liganded by ADP or ATP (26,27). To further characterize the effects of nucleotide binding to the mutants, use was made of the recent report that nucleotide binding to wild-type GroEL results in selective trypsin proteolysis at a site in the apical domains (15). Consistent with this previous report for wild type, the mutants were protected from trypsin digestion when liganded by Mg 2ϩ and became susceptible to proteolysis upon addition of nucleotide (data not shown).…”
Section: The Y203w and Y360w Mutants Of Groel Exhibit Functional And supporting
confidence: 73%
See 2 more Smart Citations
“…These results are compatible with those reported for wild-type GroEL liganded by ADP or ATP (26,27). To further characterize the effects of nucleotide binding to the mutants, use was made of the recent report that nucleotide binding to wild-type GroEL results in selective trypsin proteolysis at a site in the apical domains (15). Consistent with this previous report for wild type, the mutants were protected from trypsin digestion when liganded by Mg 2ϩ and became susceptible to proteolysis upon addition of nucleotide (data not shown).…”
Section: The Y203w and Y360w Mutants Of Groel Exhibit Functional And supporting
confidence: 73%
“…In fact, several studies using cryo-electron microscopy have demonstrated quaternary structural changes in the tetradecamer where the monomers of one ring pivot with respect to the other ring and the apical domains swing outward upon ATP and GroES binding (16,17). Similarly, recent work showed that a unique proteolytic site for trypsin at Arg-268 becomes exposed in the apical domains of one heptamer upon nucleotide binding (15). These results all confirm the original finding that nucleotides induce asymmetry between the two heptameric rings, and partially explain the finding in terms of structural changes in the oligomer (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to CCT, which was equally susceptible to proteolysis in the presence and absence of magnesium. In the presence of nucleotides (MgATP, MgADP, or MgAMP-PNP), one predominant site in the apical domain (Arg268) of each subunit of one heptameric ring of GroEL becomes susceptible to proteolysis (Gibbons & Horowitz, 1996). These results demonstrate that, like in the case of CCT, binding of nucleotides to GroEL induces conformational changes in the apical domains.…”
Section: Discussionmentioning
confidence: 81%
“…Many previous studies have reported the highest efficiencies of electroreduction of carbon dioxide reduction in bicarbonate solutions. 7 Although the available free carbon dioxide concentration in 1 M sodium bicarbonate ͑pH = 8͒ is approximately 0.5 ϫ 10 −4 mol/liter, this concentration of carbon dioxide is sustained by the relatively fast dissociation of bicarbonate, 22 ensuring carbon dioxide availability at the rate limited by this dissociation reaction. However, as the bicarbonate is used up by the electroreduction of carbon dioxide, the rate of diffusion of bicarbonate would limit the partial current density for the electroreduction of carbon dioxide.…”
Section: A170mentioning
confidence: 99%